Fundamental study Of DC and AC electrical response on a heterojunction device (AL/ZNOPTAA/METAL) for Optoelectronic Application - Abdul Ismail Abdul Rani (2019)
The combination of organic and inorganic semiconductor materials has unlocked new achievements in the performance of semiconductor devices. In the recent years, technology of hybrid material system consisting of inorganic-organic semiconductors has sufficiently evolved and is becoming popular among researchers. The inorganic semiconductors form huge crystalline networks with strong covalent or ionic bond when deposited onto a substrate layer. The organic semiconductors with smaller molecules, layers itself onto the inorganic film produces a strong grip at the interface. This property leads to a higher electrons and holes carrier mobility in the device. However, all organic based device has been limited by low speed of constituent organic devices and inorganic devices has several disadvantages for high frequency rectification due to their poor current density and low rectification ratio. Therefore, this research focuses on a hybrid inorganic-organic diode composed of two materials with different structural and optical properties. The diode is combination of Zinc Oxide (ZnO) and Polytriarylamine (PTAA) conjugated polymer acting as n-type and p-type semiconductor materials, respectively. Morphology ZnO and PTAA thin films were fabricated by varying the spin speed and temperature using combination of RF sputtering and spin coating techniques repeatedly. The hybrid diode was design by forming a PTAA-ZnO layer in between indium tin oxide (ITO) and aluminium electrode (Al) based on spin speed of 1000 and 2000 rpm with annealing temperature of 100 to 150°C. The X-ray diffraction pattern for ZnO clearly showed a broad diffraction peak at 34.2°. Meanwhile, the PTAA film depicted a broad peak between the angles of 23° to 25°. Besides that, both materials presented a transmittance about 80% and above in the wavelength range of 370 to 850 nm using UV-vis spectrometer. The surface morphological of both thin films was observed using an advanced material microscope (HIROX). The images of ZnO-PTAA thin films indicated the layer of PTAA change colour from light blue to yellowish as the annealing temperature increases, which shows a degradation over high temperature. Furthermore, as the spin speed increases, the distribution is homogenously distributed on the surface of ZnO. The current-voltage (I-V) characteristics were measured using Keithley 2400 source meter from -4.0 to 4.0 V. The turn-on voltages are varying from 1.4 V to 2.5 V depending on crystallinity and homogenous distribution of thin films. Lastly, the frequency dependent electrical response was measured using precision LCR meter in the frequency range up to 100 KHz with various bias voltages of 1.0 to 5.0 v. The results revealed that capacitance was independent towards the high frequency level of 10 Hz to 100 KHz but conductance and series resistance are strongly dependent on the frequency and bias voltage. In conclusion, combination of ZnO and PTAA semiconductors for a heterojunction device showed unique structural and optical properties and significantly improve the electrical properties due to the extended framework of the PTAA with fusion of high crystallinity structure of ZnO on thin film uniformity and performance stability.